DEVELOPING INDEPENDENCE VALUE IN EARLY CHILDHOOD - Rusmiati, Antung; Aslamiah; Wahyu; Muthalib , Arifin Abdul (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
The study aimed to describe and analyze the implementation strategy of independence values in learning activities as well as it's supporting and inhibiting factors through the application of a qualitative approach with a multi-site design. Data collection techniques used include interviews, observations, and document studies and the data obtained were individually analyzed before a cross-site data analysis was applied. The results showed the strategy to implement the development of children?s independence value at TK Negeri Pembina Rantau and TK Penerus Bangsa PGRI was integrated into learning activities through habituations, both by teachers at school and parents at home. It was conducted through daily, weekly, monthly, and annual activities. As a result, children's independence values have been successfully well-developed. Several supporting factors for this development include parents, environment, facilities and infrastructure, qualified teachers, and collaboration with outside institutions. However, several factors also inhibit this development and they include less supportive parents, as well as children?s particular emotions and conditions.